2020
DOI: 10.1109/access.2020.2999963
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Game Theory Application Research in Safety Management

Abstract: There are many heterogeneous roles involved in safety management. The behaviour interaction and strategic interactions among them will have an important impact on safety processes in the execution phase. Game theory is a powerful method for clarifying the influence mechanism and is currently experiencing rapid growth in operations, planning and management, as well as in safety management. To comprehensively sort out the current situation of game theory in safety management and finally find out the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 55 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Game theory is a research method that uses mathematical models to describe the strategic interaction between independent players. It provides optimal decision-making strategies for game players by simulating the situation in the model and has been applied in studying the formation mechanism of coal mine workers' unsafe behaviors ( 75 ). Yu et al ( 76 ) studied the symmetry of behavioral benefits of coal miners by using game theory and reported that the stability of safety behavior can be improved by adjusting the symmetry of income between managers and workers through dynamic incentives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Game theory is a research method that uses mathematical models to describe the strategic interaction between independent players. It provides optimal decision-making strategies for game players by simulating the situation in the model and has been applied in studying the formation mechanism of coal mine workers' unsafe behaviors ( 75 ). Yu et al ( 76 ) studied the symmetry of behavioral benefits of coal miners by using game theory and reported that the stability of safety behavior can be improved by adjusting the symmetry of income between managers and workers through dynamic incentives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al ( 37 ) established a signal transmission game between miners and managers based on the game theory model to test the influence of managers' emotions on miners' behaviors. Meng et al ( 75 ) reviewed relevant articles on game theory and safety management during 2010–2019 and affirmed that the application of game theory in safety management research is conducive to determine the causes and motivations of unsafe behaviors. Li et al ( 79 ) also discussed the use of evolutionary game theory to describe the interaction between stakeholders in China's coal mine safety production system, including organizations, front-line miners, and front-line managers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Models based on game theory may have some diagnostic uncertainty due to the difficulty of modeling individual variables on the other party's intentions to comply with occupational safety requirements, but this interaction can be modeled by games with incomplete information [12,14].…”
Section: Analysis Of the Latest Researches And Publicationsmentioning
confidence: 99%
“…Some studies indicated that rentseeking behavior led to great fluctuations in productivity in Chinese coal mine safety Construction safety supervisory mechanism supervision (Chen et al, 2016). In a similar vein, the collusion between the GC and the SE wildly exists in construction safety supervision (Meng et al, 2020). The existence of rentseeking renders safety supervision, a mere formality because SE may conceal potential safety hazards or ignore faults in projects, which increases the likelihood of accidents.…”
Section: Introductionmentioning
confidence: 99%